Electroanalysis of formetanate hydrochloride by a cobalt phthalocyanine functionalized multiwalled carbon nanotubes modified electrode: characterization and application in fruits. (10th March 2016) - Ribeiro, Francisco Wirley Paulino; de Souza Lucas, Francisco Willian; Mascaro, Lucia H.; Morais, Simone; da Silva Casciano, Paulo Naftali; de Lima-Neto, Pedro; Correia, Adriana N.
Graphical abstract: Highlights: A Co-phthalocyanine functionalized MWCNT modified carbon electrode was developed. Formetanate (FMT) electroanalytical behavior is consistent with an ECE mechanism. CoPc- f MWCNT/GCE exhibited good analytical performance to quantify FMT. CoPc- f MWCNT/GCE was successfully applied to fruits (recoveries ≥ 94.2%). Abstract: This study characterizes the electroanalytical behavior of the carbamate pesticide formetanate hydrochloride (FMT) at a cobalt phthalocyanine (CoPc) functionalized multiwalled carbon nanotubes ( f MWCNT) modified glassy carbon electrode (CoPc- f MWCNT/GCE). Nafion ® was used to improve solubility and dispersibility of f MWCNT. The construction of the developed electrode was characterized by high-resolution field-emission gun scanning electron microscopy, Raman spectroscopy, cyclic voltammetry and electrochemical impedance spectroscopy. FMT exhibited a behavior consistent with a three-step reaction of the electrochemical-chemical-electrochemical mechanistic type at CoPc- f MWCNT/GCE (three anodic peaks at 0.26, 0.55 and 1.2 V, and two cathodic peaks at 0.35 and 0.50 V vs . Ag/AgCl/3 M KCl). Highly reproducible and well-defined peaks were obtained at the optimum experimental conditions (Britton-Robinson buffer at pH 5.0, accumulation potential 1.55 V, accumulation time 5 s, frequency 100 s −1, amplitude 30 mV, and scan increment 3 mV). Peak currents were found to be proportional to the FMT concentrations in the range of 9.80 × 10 −8 to 3.92 × 10 −6  mol dm −3 with a detection limit (LOD) of 9.7 × 10 −8  mol dm −3 . The modification of GCE with CoPc- f MWCNT enhanced the electrocatalytic activity and provided high sensitivity (3.51 A mol −1  dm 3 ). The developed electroanalytical methodology was successfully applied to FMT residue analysis in mango and grape samples with recoveries in the range of 94.2 ± 4.5 to 105.7 ± 1.8%. The proposed electroanalytical approach represents a reliable, sensitive and environmental friendly analytical alternative for determination of FMT.